PERCEPTIONS OF COMMUNICATION EFFICACY AMONG AFGHANISTAN GOVERNMENT EMPLOYEES AND THEIR CUSTOMERS - Abolfazly, Mahdi (Electronic Journal of Business and Management, 2021)
A significant communication gap exists between Afghanistan government employees and their customers (citizens). This qualitative study investigates the reasons behind this gap and explores ways to increase engagement. Interviews were conducted with 12 individuals, including both government employees and customers in Afghanistan. Using thematic analysis, the study found that the gap is primarily caused by a mutual lack of knowledge regarding government work procedures and a deficiency in communication skills. This lack of proficiency has led to a decline in public trust. The research concludes that closing this gap requires government-led initiatives to improve employee behavior and communication knowledge, alongside efforts to educate the public on administrative processes.